KONFLIK SOSIAL PASCA PEMILIHAN LEGISLATIF (DPRD KABUPATEN INDRAGIRI HULU) DI DESA TANAH DATAR KECAMATAN RENGAT BARAT - Sari, Desy Maya; Jalil, Ashaluddin (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2015)
This research was conducted in the village in the district of Tanah Datar Rengat Barat. This village was chosen, due to take place after the legislative elections occurred continuing conflict between the supporters of the legislative. The aim of this study was to determine the continuing conflict of legislative elections and to find out what is causing the conflict and efforts made in the resolution of conflicts in the society.The population in this study were all successful teams of each legislative candidates, the public and legislative candidates. Not all are taken into subjects but is determined as candidates involved, a successful team leader of each candidate, the head of the village and some community leaders were familiar with the state of research areas.Determination of the subject in focus to the team success of each legislative candidates. Successful team from the Golkar party amounting to two subjects and successful team of PDI-P totaling two subjects, and public figures amounted to four subjects, and then both legislative candidates elected regional peopleâs representative assembly.Methods This study was conducted by researchers using qualitative methods therefore approach used is a qualitative approach. Meaning a qualitative approach was carried out to study and find out how the attitude of the subject towards the implementation of the legislative elections and post-election.Keywords: Social Conflict, Legislative